Assesment of group regulation feasibility in thermal power plant auxiliaries capacity control - Vanin, Viktor; Lasurenko, Oleksandr; Kruhol, Mykola (Eastern-European Journal of Enterprise Technologies, 2020)
The method of group capacity regulation of centrifugal mechanisms is proposed to solve the problem of increasing the energy efficiency of thermal power plant auxiliaries. The method is based on using a group frequency converter for basic capacity regulation of centrifugal mechanisms. Additional regulation is commonly carried out by throttling, bypassing or changing the guide vane opening angle. Analysis of auxiliary power consumption showed that due to ineffective regulation methods, the share of power consumption can reach 50 %. A mathematical model of the centrifugal mechanism that allows for studying various regulation methods is developed. The task of finding optimal control parameters for a group of centrifugal mechanisms that ensure power boiler operation is stated and solved. By the results obtained, it was determined that group capacity regulation of boiler draft mechanisms is most rational. For the feed pump, an individual variable-frequency drive shall be used. In contrast to the individual variable-frequency drive, the introduction of the group regulation method requires less investment. This method can significantly reduce the auxiliary power consumption of thermal power plants. The projected decrease in auxiliary power consumption is 10.7 %. The results show the high efficiency of the group capacity regulation of centrifugal mechanisms, so this method can become a promising direction in increasing the energy efficiency of thermal power plants